Credit and Fiscal Multipliers in China - Chen, Sophia (IMF Working Papers; Working Paper, 2017)
We jointly estimate credit and fiscal multipliers in China. We use the tenure of the provincial party secretary, interacted with the type of stimulus used in other provinces, to obtain separate instruments for provincial credit and government expenditure. We estimate a fiscal multiplier of 0.8 and a credit multiplier of 0.2 in 2001-2015. The multipliers have changed over time. The fiscal multiplier has increased from 0.75 in 2001-2008 to 1.4 in 2010-2015. The credit multiplier has declined from 0.17 to zero over the same periods. Our results suggest that reducing credit growth in China is unlikely to disrupt output growth, whereas fiscal policy may be effective in supporting macroeconomic adjustment.